SAT0080 COMPARATIVE ANALYSIS OF FRAGILITY FRACTURE IN PATIENTS WITH ELDERLY ONSET RHEUMATOID ARTHRITIS AND YOUNG ONSET RHEUMATOID ARTHRITIS. (2nd June 2020) - Kozhevnikova, P.; Dydykina, I.; Kovalenko, P.; Lila, A.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic autoimmune disease, characterized by erosive arthritis and systemic organ involvement. Chronic inflammation, long RA disease duration, decreased physical activity, immobilization, glucocorticoids use lead to local (periarticular osteoporosis) and generalized loss of bone tissue, decrease in bone mineral density, contravention of microarchitectonics and increased risk of fragility (low-energy) fractures. The structure and density of bone tissue at elderly onset RA, in addition to the above factors, are affected by comorbid diseases, sex steroids level decrease and molecular changes in bone tissue, specifically attributed to aging, followed by increased bone resorption. Fractures reduce the quality of life, have a negative impact on the course of the underlying and concomitant diseases. Objectives: Сompare frequency of fragility fracture in patients with elderly onset rheumatoid arthritis and young onset rheumatoid arthritis. Methods: We included 474 patients with RA diagnosed at 25– 78 years old and fulfilled the American College of Rheumatology (formerly American Rheumatism Association) classification criteria for RA revised in 1987. The patients were divided into two groups depending on age at the RA-onset: The first group (group I) included 217 patients with young onset RA (at 25 to 44 years), second group (group II) included 66 patients with elderly onset RA (aged ≥60 years). The distribution of patients into groups was consistent with the age classification of the World Health Organization. In total, it was selected 283 RA patients. The mean age in group I was 50.4 years, in group II - 71.2 years. The mean age at the onset of RA in group I was 35.0 years, in group II - 66.2 years.; RA duration was 14.4 years and 4.6 years, respectively. Long-term history of glucocorticoids use (for more than 3 months) was observed in 50% of patients in group I, and in 42% of patients in group II. Results: 40 (18%) patients in group I and 17 (26%) patients in group II had fragility fractures. Among patients with fragility fracture, 23 (57, 5%) patients in group I and 6 (35%) patients in group II received glucocorticoid therapy for more than 3 months. Two or more fractures in history had 16 (40%) in group I, and 3 (18%) in group II. Conclusion: The frequency of fragility fracture in the study groups was comparable (p> 0.05), despite the age of patients. But, the frequency of refractures was higher in patients with RA-onset at young age, which, apparently, is a consequence of long RA disease duration and use of glucocorticoids. Disclosure of Interests: None declared